INFLUENCE OF DIFFERENT QUALITY OF BUFFALO OOCYTES ON JN - VITRO MATURATION AND FERTILIZATION - SINGH, R P; SHAH, R G; TANK, P H (The Indian Journal of Animal Reproduction, 2023)
The study was conducted on 499 freshly collected abattoir ovaries of Surti buffaloes. The total number ofdifferent grades of oocytes recovered by slicing method was 1046. The mean numbers of oocytes per ovary ofgradeA(2.92 ± 0.14) and B (2.49 ± 0.13) were significantly higher (P3 layer of cumulus cells) andgrade B (1-3 layer of cumulus cells) quality of oocytes attained good cytoplasmic maturation than grade C (lesscompact cumulus cells) and grade D (nude oocytes). The total maturation rate from gradeAoocytes was highest(87.94 %) followed by oocytes of grade B (82.91 %) and grade C (72.22 %). The nuclear maturation was evaluatedin 528 oocytes by Hoechst 33342 stain. The highest number of gradeAoocytes (26.00 %) reached to M-ll stage,followed by grade B (24.21 %) and grade C (14.28 %) and none of the oocytes from grade D reached to M-11 stage;they were mainly arrested at GV and GVBD stage. Oocytes of grade A (n=181) and B (n::::305), which hadcytoplasmic maturation, were utilized for in-vitro fertilization. The overall fertilization rate observed was 20.16 percent for grade A and B oocytes. The higher fertilization rate was observed for grade A(21.00 % ) oocytes than thatin grade B (19.67 %). The study revealed that the presence of cumulus layer around the oocytes affected thematuration and fertilization rate of buffalo oocytes. Significantly (P
Keywords: Buffalo oocytes; In-vitro maturation; In-vitro fertilization; Cumulus Cells; TCM-199 media